Lifestyles and health-related quality of life in Chinese people: a national family study - Zou, Shiqian; Feng, Guanrui; Li, Danyang; Ge, Pu; Wang, Siyi; Liu, Tinlun; Li, Haijun; Lai, Yongjie; Tan, Zijian; Huang, Yuling; Huang, Jian; Zhang, Casper; et al. (BMC public health, 2022)
There were few studies that investigated health-related quality of life (HRQoL) of the general population in China, and many of them reported limitations in sampling. To investigate the relationship between lifestyles and HRQoL in the Chinese population in both individual and family levels. Online questionnaires were distributed across China to collect demographic information and participants' HRQoL using EuroQoL 5 Dimension scales. The EuroQoL Group's 5 Dimension scale (EQ-5D) index and EuroQoL Group's visual analog scale (EQ VAS) score were calculated to evaluate the HRQoL. A total of 1305 valid questionnaires were included. Higher HRQoL was found in people with intend to lower oil intake, intend to lower salt intake, intend to lower sugar intake, balanced diet, moderate sports every week, a sport hobby and joining a fitness organization (all p<.05). HRQoL was higher among male (female as reference), healthy weight (unhealthy weight as reference) (both p<.05). Negative correlation was found between HRQoL and clinical medical history and drinking history. Small families (1-2 persons, 83.19 ± 20.14) had poorer HRQoL (EQ VAS score) than big families (≥3 persons, 85.00 ± 17.96, p <.05). In China, people with healthy dietary habits, regular sports habits, healthy weight and male groups tended to have better HRQoL. Clinical medical history and drinking history were negatively related to HRQoL. Small families tend to have poorer HRQoL than big families. The finding implicated influence of the number of family members on people's perception of health and provided scientific evidence for the current policies to encourage birth in China. For a better HRQoL, we suggest people live in big families and take measures to lower salt/sugar/oil intake and exercise regularly in daily life.